Two new species of Indigofera (Leguminosae—Papilionoideae) from Thailand - Matttapha, Sawai; Chantaranothai, Pranom (Phytotaxa, 2013)
Two new species of Indigofera, I. smitinandii and I. udonthaniensis from Thailand are described and illustrated.